Tax avoidance analysis: The role of institutional ownership and fiscal loss compensation - Kusumawardhani, Adhityawati; Jing Ying, Amanda Kwan; Yennisa, Yennisa (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2025)
This research aims to examine how tax avoidance in manufacturing firms listed on the Indonesia Stock Exchange is impacted by institutional ownership and financial loss compensation. Because a lower ETR score indicates a larger degree of tax avoidance by the corporation, ETR is used in this study as a proxy for tax avoidance. Multiple linear regression analysis is employed as part of a quantitative research methodology. One hunderd thirty-nine companies were chosen for the sample using purposive sampling throughout the 2018-2021 observation period. The findings demonstrated that the company’s propensity to evade taxes is only marginally correlated with institutional ownership. Even while tax avoidance is also greatly impacted by fiscal loss compensation, this indicates that businesses use fiscal loss accumulation as a tool to lessen tax avoidance. The findings of this study point to the necessity of strong corporate governance and financial control in discouraging tax avoidance practices and informing authorities about the fiscal loss compensation provisions in Indonesia’s tax system.